Efficient and Informative Laboratory Testing for Rapid Confirmation of H5N1 (Clade 2.3.4.4) High-Pathogenicity Avian Influenza Outbreaks in the United Kingdom - Marek J. Slomka; Scott M. Reid; Alexander M. P. Byrne; Vivien J. Coward; James Seekings; Jayne L. Cooper; Jacob Peers-Dent; Eric Agyeman-Dua; Dilhani de Silva; Rowena D. E. Hansen; Ashley C. Banyard; Ian H. Brown (Viruses, 2023)
During the early stages of the UK 2021-2022 H5N1 high-pathogenicity avian influenza virus (HPAIV) epizootic in commercial poultry, 12 infected premises (IPs) were confirmed by four real-time reverse-transcription–polymerase chain reaction (RRT)-PCRs, which identified the viral subtype and pathotype. An assessment was undertaken to evaluate whether a large sample throughput would challenge laboratory capacity during an exceptionally large epizootic; hence, assay performance across our test portfolio was investigated. Statistical analysis of RRT-PCR swab testing supported it to be focused on a three-test approach, featuring the matrix (M)-gene, H5 HPAIV-specific (H5-HP) and N1 RRT-PCRs, which was successfully assessed at 29 subsequent commercial IPs. The absence of nucleotide mismatches in the primer/probe binding regions for the M-gene and limited mismatches for the H5-HP RRT-PCR underlined their high sensitivity. Although less sensitive, the N1 RRT-PCR remained effective at flock level. The analyses also guided successful surveillance testing of apparently healthy commercial ducks from at-risk premises, with pools of five oropharyngeal swabs tested by the H5-HP RRT-PCR to exclude evidence of infection. Serological testing at anseriform H5N1 HPAIV outbreaks, together with quantitative comparisons of oropharyngeal and cloacal shedding, provided epidemiological information concerning the chronology of initial H5N1 HPAIV incursion and onward spread within an IP.